O papel das emissoras educativas no Brasil em tempo de eleições - Burini, Débora; Moura, Jefferson José Ribeiro de; Affini, Leticia Passos [UNESP] (My University, 2011)
The concept of educational radio is present in the Brazilian Code of Broadcasting in 1963, valued by an Interministerial 1999.According to the Ministry of Communications, only 176 stations are considered educational universe of 3,000 existing radios in Brazil. In this context, the study proposes to establish a discussion on the educational experiences obtained from the radio, considering the Brazilian radio culture that favors concessions to trade groups and religious politicians. The challenge will be to move toward a program that combines educational content, entertainment, and thus ensures a common universe of communication skills enabling the adult radio listeners their actual interaction with the world around him. The methodology will work in the literature from texts on the subject, and the result of practical observations collected during visits to the broadcasters, programming and analysis.

O conceito de rádio educativa está presente no Código Brasileiro de Radiodifusão de 1963, valorizado por uma Portaria Interministerial de 1999. Segundo dados do Ministério das Comunicações, apenas 176 emissoras são consideradas educativas do universo de 3 mil rádios existentes no Brasil. Nesse contexto, o estudo propõe estabelecer uma discussão sobre as experiências educativas obtidas a partir do rádio, considerando a cultura radiofônica brasileira, que privilegia concessões para grupos comerciais e de políticos religiosos. O desafio será avançar em direção a uma programação que alie entretenimento ao conteúdo educativo, e assim garanta um universo comum de competências comunicativas permitindo ao radiouvinte adulto sua real interação com o mundo que o cerca. A metodologia adotada no trabalho vai da pesquisa bibliográfica a partir de textos sobre o tema, bem como do resultado de observações práticas colhidas nas visitas as emissoras, e análise de programação.
Keywords: Communication; Education; Radio; PublicSpace; Comunicação; Educação; Rádio; Espaço público